Microsoft Dynamics CRM 2015 application design : master professional-level business application design using Microsoft Dynamics CRM 2015 and its xRM features /: master professional-level business application design using Microsoft Dynamics CRM 2015 and its xRM features. (2015) - Pal, Mahender
No abstract available